(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In recent years, isolated studies have appeared showing a high prevalence of CKD among patients with chronic obstructive pulmonary disease (COPD), reaching 20 to 53%, which is comparable with the data for arterial hypertension and diabetes mellitus [20]. Currently, COPD is considered a disease with pronounced systemic manifestations, which contributes to the development of a number of concomitant diseases, such as cardiovascular diseases, skeletal muscle dystrophy and osteoporosis [1, 17]. CKD and COPD have common risk factors - smoking, chronic inflammation, development of endothelial dysfunction, increased activity of the renin- angiotensin - aldosterone system (RAAS), neurohumoral imbalance, development of nutritional deficiency, creating conditions for the development and progression of CKD [7, 20].